Managemen Pembelajaran Bahasa Inggris dalam Meningkatkan Capaian Pembelajaran Selama Pandemi Covid-19 di Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang - Rachma Putri Kasimbara (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2021)
Introduction The objective of this study was to determine the effectiveness of distance learning during the Covid-19 pandemic in, managing English classes and improving student performance at ITSK RS dr. Soepraoen. Method used is descriptively qualitative, with data collection techniques through interviews and observations. The research subjects were English teachers and deputy directors of ITSK RS dr. Soepraoen. The results of the study are as initially, English education planning will be based on subjects, proficiency standards, basic skills, learning objectives, teaching modules, procedures, times, learning activities, resources / learning teams and evaluation of the learning results of distance students during the Covid-Phase 19 created. Second, the implementation of the training that Teacher is attempting has been guided by the most recent updated curriculum and the Online Learning Implementation Plan. English teachers practiced groundbreaking education like Google Classroom, Zoom, WhatsApp, and many more during the Covid-19 pandemic. The distance learning used by the teacher consists of opening the class, providing modules or classroom materials two days before the learning activities and discussing learning with students where learning is centered on the student. The educational process places more emphasis on the cognitive and psychomotor areas. Third, learning assessment uses pretest and posttest when conducting online education. Conclusion The evaluation method used in learning uses direct observation, doing tests / exercises at the end of the lesson so that the teacher knows the weaknesses and measures of each student. The learning support facilities at ITSK RS dr. Soepraoen are equipped with a language lab to make the implementation of English learning more effective. Keywords: English learning, online learning study, covid-19